USING SALICYLIC ACID, FOLIC ACID AND/OR MANCOZEB IN CONTROLLING TOMATO EARLY BLIGHT BIOTIC STRESS AND THEIR EFFECTS ON GROWTH, YIELD, FRUIT QUALITY, AND STRESS-RELATED ENZYMES - Alaa El-Den H. R.,; G. M.Abd El-Wahab,; S. A. Masoud, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Two field experiments were conducted to study the effect of foliar applications of salicylic acid (200 ppm), folic acid (100 ppm) and/or Mancozeb (50% and 100% of recommended dose) on the growth, yield, quality, enzymes activities related to stress, and disease severity% of tomato plants cv. “Fayrouz” grown under biotic stress conditions of early blight (A. solani) disease. The results showed significant effects of the applied treatments on all the studied characters with a noticeable superiority of the treatments of SA+FolA+50%Rec followed by 100%Rec without significant difference between them, which reflects on high mean values of growth, chlorophyll, yield, fruit quality, total phenol, and enzymes activities, in both seasons. Also, the best-applied treatments were related with the highest significant increases in leaves’ total phenol content in addition to enhancing the activity levels of POD, PPO, and CAT enzymes, which were found to significantly decrease the disease severity%, in both seasons. It could be suggested to reduce the recommended dose of mancozeb fungicide up to 50% by using 200 ppm of salicylic acid with 100 ppm of folic acid for ameliorating the deleterious effects of early blight and producing tomato safer for human consumption and eco-friendly.